At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To complete the first space on the table, we need to replace g(x) by 7 and solve for x as:
g(x) = -4x - 1
7 = -4x - 1
7 + 1 = -4x - 1 + 1
8 = - 4x
8/(-4) = -4x/(-4)
-2 = x
So, the first space is -2
Then, for the second space, we need to replace x by 0 and calculate g(x) as:
g(x) = -4x - 1
g(x) = -4*0 - 1
g(x) = 0 - 1
g(x) = -1
So, the second space is -1
The third space is calculated as the first one, replacing g(x) by -13 and solving for x:
g(x) = -4x - 1
-13 = -4x - 1
-13 + 1 = -4x - 1 + 1
-12 = - 4x
-12/(-4) = -4x/(-4)
3 = x
So, the third space is 3
Finally, the fourth space is calculated as the second one, replacing x by -1, so:
g(x) = -4x - 1
g(x) = -4*(-1) - 1
g(x) = 4 - 1
g(x) = 3
So, the fourth space is 3
Answer:
x g(x)
-2 7
0 -1
3 -13
-1 3
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.